Clinical, morphological, CT and MRI characteristics of anterior skull base and orbital tumors (Ukrainian Journal of Ophthalmology, 2025)
Background: Tumors of the anterior skull base and orbit (ASBOT) are more commonly epithelial malignancies arising in the nasal cavity, paranasal sinuses, and orbit, and, of ASBOT, approximately 25%-30% are diagnosed in advanced cases. Primary epithelial tumors of the orbit are located in the lacrimal gland area, and grow invasively with destruction of the roof and external wall of the orbit and intracranial and intracerebral extensions.Purpose: To examine the clinical, morphological, computer tomography (CT) and magnetic resonance imaging (MRI) characteristics of anterior skull base and orbit tumors.Material and Methods: One hundred and ninety-two patients with ASBOT treated at the Kolomiichenko Institute of Otolaryngology and Romodanov Neurosurgery Institute and 110 patients with epithelial lacrimal gland tumors (PELGT) treated at the Filatov Institute were included in the study.Results: A malignant ASBOT was found in 133 patients (69.3%), and a benign, in 59 (30.7%). Most benign cases (84%) were juvenile nasopharyngeal angiofibroma, meningioma or osteoma. The most common primary location of benign ASBOT was extracranial (51% of patients), followed by skull base bone and cartilage (27%) and intracranial (22%).Cancer neoplasms constituted 40% of malignant ASBOT. The primary location of malignant ASBOT was much more commonly extracranial (81% of patients) than skull base bone and cartilage (19%). Of the 110 patients with PELGT, 51 (46.3%) had benign tumors (benign pleomorphic adenoma, 42 (38.2%); mucoepidermoid tumor, 5 (4.5%); myxoma, 3 (2.7%); and oncocytoma, 1 (0.9%)); and 59 (53.7%), malignant tumors (adenocarcinoma, 33 (30.0%); adenoid cystic carcinoma, 18 (16.4%); and malignant pleomorphic adenoma, 8 (7.3%)).Patient complaints were broadly categorized into cerebral, rhynologic, neuro-ophthalmologic and otologic. These complaints were found almost as common in patients with benign as with malignant ASBOT, and were characteristic also for PELGT. Clinical, CT and MRI features for various histomorphological types of benign and malignant neoplasms were described.Conclusion:  Large and even giant size is a common feature of ASBOT; this is true also for primary ASBOT diagnosed for the first time during a long asymptomatic stage. We also determined frequencies of injury to various compartments of the intra- and extra-cranial surfaces of the skull base for benign and malignant processes. Benign ASBOT were found to be more commonly located in the lateral skull base, whereas malignant ASBOT were more commonly seen within the floor of the anterior cranial fossa. There are certain grades of intracranial growth for malignant ASBOT and intracranial extension for benign ASBOT, these grades depending mostly on histobiological characteristics and disease duration. Intracranial and intracerebral extensions are the main cause of mortality in patients with PELGT.
Keywords: benign and malignant anterior skull-base tumors; epithelial lacrimal gland tumors; clinical features; CT; MRI; diagnostic techniques